Cardiac resynchronization therapy with defibrillator in ischemic versus nonischemic cardiomyopathy - Yücel, Gökhan; Gaasch, Leo; Hetjens, Svetlana; Oeztuerk, Oezge Nur; Yildirim, Gamze; Pfleger, Stefan; Dürschmied, Daniel; Akın, Ibrahim; Kuschyk, Jürgen (International heart journal, 2024)
Cardiac resynchronization therapy with implantable cardioverter defibrillators (CRT-Ds) are established therapy options for patients suffering from heart failure (HF). Several aspects of HF modification have yet to be described regarding etiology-dependent outcome differences in the long-term.The Mannheim CArdiac Resynchronization TherApy RetrospeCtive ObservAtioNAl (MARACANA) Registry retrospectively included all patients provided with CRTs in our center from 2013 to 2021. CRT-D recipients (n = 380) were grouped to either ischemic cardiomyopathy (ICM, n = 206) or nonischemic cardiomyopathy (NICM, n = 174). Both groups were compared regarding survival, left ventricular ejection fraction (LVEF), hospitalizations due to HF, intrinsic and paced QRS width, NYHA classification, and several further aspects of HF modification in the long-term (59.1 ± 4.81 months).Patients with ICM were older (73.3 ± 8.4 versus 67.7 ± 10.8 years) and predominantly male (86.4 versus 74.7%) and presented with higher creatinine values (1.57 ± 0.92 versus 1.31 ± 0.66 mg/dL, each P < 0.05) at baseline. The mean survival for patients with NICM was better (51.9 ± 1.2 versus 54.4 ± 1.1 months, P = 0.03). Improvements in NYHA (2.93 ± 0.4 versus 2.79 ± 0.5-2.19 ± 0.7 versus 1.79 ± 0.7) and LVEF (26.4 ± 6.8 versus 27% ± 6.9% to 35.7 ± 9.6 versus 44 ± 11%, each P < 0.05) were similar for both groups after 5 years. Patients with ICM experienced more hospitalizations due to HF within the first year (odds ratio 1.9, P < 0.05), whereas electrical remodeling was more impressive for NICM (QRS width 157.1 ± 19.4 milliseconds versus intrinsic 116.6 ± 12.7 milliseconds and paced 131.9 ± 21 milliseconds after 5 years, both P < 0.05).Patients with HF might experience long-term improvements in functional status and left ventricular reverse remodeling following CRT-D, regardless of underlying etiology. Alterations in some aspects of HF modification could be influenced by time- and etiology-associated comorbidities.